2013
DOI: 10.1371/journal.pone.0059581
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fat Content and Fiber Type Modulate Hind Gut Microbial Community and Metabolic Markers in the Pig

Abstract: Obesity leads to changes in the gut microbial community which contribute to the metabolic dysregulation in obesity. Dietary fat and fiber affect the caloric density of foods. The impact of dietary fat content and fiber type on the microbial community in the hind gut is unknown. Effect of dietary fat level and fiber type on hindgut microbiota and volatile fatty acid (VFA) profiles was investigated. Expression of metabolic marker genes in the gut, adipose tissue and liver was determined. A 2×2 experiment was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
87
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(102 citation statements)
references
References 48 publications
15
87
0
Order By: Relevance
“…Irrespective of line, there was a marked decrease in BW and body fat content with the HF diet. This observation is in agreement with previous studies showing a negative effect of fibre inclusion in high-fat diet on adiposity in pigs [26,27] and rats [28]. Fig.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Irrespective of line, there was a marked decrease in BW and body fat content with the HF diet. This observation is in agreement with previous studies showing a negative effect of fibre inclusion in high-fat diet on adiposity in pigs [26,27] and rats [28]. Fig.…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, the lower plasma concentration of β-hydroxybutyrate observed with the HF diet may sign for a variation in the hepatic oxidation of fatty acids. Previous studies have suggested that insoluble fibres induce fatty acid oxidation in the liver of mice [31] and pigs [27]. Altogether, these findings support the view that the HF diet can drive different metabolic changes at the hepatic level.…”
Section: Discussionsupporting
confidence: 85%
“…However, the CMC is a low-fermentable and high-viscous carboxymethylcellulose and increases the AID of CP in weaned pigs (Fledderus et al, 2007). The INU is a highfermentable, low-viscous fructan (Yan et al, 2013) and is fermented by microbial populations (Bach Knudsen and Hansen, 1991). The present study was designed to study the effects of incorporation of 5% INU or CMC into a corn-soybean meal diet of finishing pigs.…”
Section: Discussionmentioning
confidence: 99%
“…The INU with low viscosity increases digesta passage rate (Yan et al, 2013). Quick digesta passage rate causes less time for substrate digested by CHO enzymes (Hooda et al, 2011), thereby reducing 9.4% of the CHO ileal digestibility compared to the control diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation